2020
DOI: 10.3390/ma13245630
|View full text |Cite
|
Sign up to set email alerts
|

Catalyst-Less and Transfer-Less Synthesis of Graphene on Si(100) Using Direct Microwave Plasma Enhanced Chemical Vapor Deposition and Protective Enclosures

Abstract: In this study, graphene was synthesized on the Si(100) substrates via the use of direct microwave plasma-enhanced chemical vapor deposition (PECVD). Protective enclosures were applied to prevent excessive plasma etching of the growing graphene. The properties of synthesized graphene were investigated using Raman scattering spectroscopy and atomic force microscopy. Synthesis time, methane and hydrogen gas flow ratio, temperature, and plasma power effects were considered. The synthesized graphene exhibited n-typ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 70 publications
1
17
0
Order By: Relevance
“…The polarization states of O light and E light in the crystal are expressed in Equation (8). Because the basis vectors are e 1 = (100), e 2 = (010), and e 3 = (001) in the sample coordinate system X-Y-Z, the crystal Jones matrix is inferred in the sample coordinate system X-Y-Z [18], as shown in Equation (9).…”
Section: Raman Intensity Theory Of Sicmentioning
confidence: 99%
See 1 more Smart Citation
“…The polarization states of O light and E light in the crystal are expressed in Equation (8). Because the basis vectors are e 1 = (100), e 2 = (010), and e 3 = (001) in the sample coordinate system X-Y-Z, the crystal Jones matrix is inferred in the sample coordinate system X-Y-Z [18], as shown in Equation (9).…”
Section: Raman Intensity Theory Of Sicmentioning
confidence: 99%
“…Due to its nondestructive, noncontact, in situ, and highly sensitive characteristics, Raman spectroscopy has been successfully applied to the field of semiconductor materials and two-dimensional materials [4][5][6]. The Raman spectra of semiconductor crystals contain structural and physical information, including crystal orientation [7], doping [8], grain size [9], stress/strain [10], and electron mobility [11]. Therefore, these properties can be characterized by quantitative analysis of the intensity, wavenumber, full width at half maximum (FWHM), and symmetry through the Raman spectra of the samples.…”
Section: Introductionmentioning
confidence: 99%
“…In this case, c � φ. e Raman intensity of each Raman mode is expressed as (11) when α is fixed but φ is rotated (φ � c) and as (12) when φ is fixed (φ � c) but α is rotated. e corresponding changes in the distributions with φ are shown in Figure 3…”
Section: Hh Casementioning
confidence: 99%
“…e Raman spectrum of semiconductor crystals contains structural and physical information, including the crystal state [8,9], crystal plane [10], doping [11], grain size [12], stress/strain [13], Fano resonance [14], and electron mobility [15]. Hence, it is possible to characterize these properties using specific theories of Raman spectroscopy by quantitatively analyzing the wavenumber, intensity, full width at half maximum (FWHM), and symmetry in the Raman spectra from the samples.…”
Section: Introductionmentioning
confidence: 99%
“…In the plasma discharge process, when the gas between the cathode and the anode is activated by the arc-discharge, a hexagonal arrangement of carbon atoms is observed, resulting from the nucleation and rearrangement of individual carbon atoms that have evaporated at the anode and cathode. Gudaitis et al [ 15 ] demonstrated that graphene can be grown on the Si (100) substrates. More in detail, few-layer graphene was synthesized from CH 4 and H 2 on the Si (100) substrates without the use of catalysts via the use of direct microwave plasma-enhanced chemical vapor deposition (PECVD).…”
mentioning
confidence: 99%